Learning The English Language Beside On Storytelling In Early Childhood - Baik Wardatul Husna; Zulkarnaen Zulkarnaen (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2023)
This study was a literature review about learning the English language based on storytelling in early childhood. Storytelling has the original form of teaching and fostering emotional intelligence potential. Storytelling help the child gain insight into human behavior and promotes language learning by enriching learner vocabulary and acquiring new language structures. There are three main dimensions in which stories can add to learning in the school curriculum: stories can be used to reinforce conceptual development in children, means of developing learning and carefully selected stories can also be used to develop other subjects in the curriculum.Â  In the classroom, storytelling and reading stories aloud are key elements of language teaching. Creating, recalling and repeating stories is a learning process for teachers as well as for students. So that teacher must know technique teaching English through storytelling in the classroom include: preparation, in the lesson and after story.